China - Africa Relations: In Search of a New Model for Cooperation - Joneva, Elizabet (Research Papers, 2018)
In the last decade, the subject of China-Africa relations provokes special attention on a global level in view of the new dimensions of Beijing’s involvement in the world. China is facing the challenge to adapt to new geopolitical and geoeconomic realities and the undertaken measures transform its approaches towards different regions. In the light of these trends, the paper explores the principal vectors of China’s cooperation with Africa with specific aim to compare it with the strategies of the EU.
Keywords: Cooperation; Africa; China; Foreign policy; Energetics